eComplexity: validation of a complex thinking instrument from a structural equation model - Vázquez-Parra, José Carlos; Henao-Rodriguez, Linda Carolina; Lis-Gutiérrez, Jenny Paola; Castillo-Martínez, Isolda Margarita; Suarez-Brito, Paloma (Frontiers in Education, 2024)
The validation of the E-Complexity instrument, as explored in this study, holds significant implications both academically and practically. By employing Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess students' self-perceptions of their performance in complex thinking and its sub-competencies, the research advances the field of educational measurement. This innovative methodological approach, tested on data from 1,037 university students in Mexico, confirms the instrument's statistical validity and reliability. Academically, it enriches the discourse on instrument design and validation, offering a rigorous model for future efforts to measure cognitive competencies. Practically, the study's findings inform educational practice by pinpointing systemic and scientific thinking as key to developing complex thinking skills. This insight enables educators to tailor teaching strategies and curriculum designs more effectively, aiming to enhance students' ability to navigate the complexities of the modern world. The E-Complexity instrument's proven reliability as a tool for measuring perceived achievement in complex thinking provides a valuable resource for evaluating educational interventions' effectiveness.Consequently, this research contributes to a more informed approach to fostering critical thinking skills, benefiting both theoretical exploration and practical application in educational settings.